Comparison of direct‐plating and broth‐enrichment culture methods for detection of potential bacterial pathogens in respiratory secretions. Issue 11 (November 2017) - Kaur, Ravinder; Wischmeyer, Jareth; Morris, Matthew; Pichichero, Michael E.
Abstract : Objective. : We compared the recovery of potential respiratory bacterial pathogens and normal flora from nasopharyngeal specimens collected from children during health and at the onset of acute otitis media (AOM) by selective direct‐plating and overnight broth‐enrichment. Methods. : Overall, 3442 nasal wash (NW) samples collected from young children were analysed from a 10‐year prospective study. NWs were cultured by (1) direct‐plating to TSAII/5% sheep blood agar and chocolate agar plates and (2) overnight broth‐enrichment in BacT/ALERT SA‐broth followed by plating. Standard microbiology techniques were applied to identify three dominant respiratory bacterial pathogens: Streptococcus pneumoniae (Spn), Haemophilus influenzae (Hflu) and Moraxella catarrhalis (Mcat) as well as two common nasal flora, Staphylococcus aureus (SA) and alpha‐haemolytic Streptococci (AHS). Results/Key findings. : Direct‐plating of NW resulted in isolation of Spn from 37.8%, Hflu from 13.6% and Mcat from 33.2% of samples. In comparison, overnight broth‐enrichment isolated fewer Spn (30.1%), Hflu (6.2%) and Mcat (16.2%) ( P <0.001‐0.0001). Broth‐enrichment resulted in significant increased isolation of SA (6.0%) and AHS (30.1%) ( P <0.0001). Competition between bacterial species in broth when both species were detected by direct‐plating was assessed, and it was found that SA and AHS out‐competed other species during broth‐enrichment when samples were collected from healthy children but not during AOM. In middle ear fluids (MEF) at the onset of AOM, broth‐enrichment resulted in higher recovery of Spn (+10.4%, P <0.001), Hflu (+4.4%, P =0.39) and Mcat (+13.5%, <0.001). Conclusion. : Broth‐enrichment significantly reduces the accurate detection of bacterial respiratory pathogens and increases identification of SA and AHS in NW. Broth‐enrichment improves detection of bacterial respiratory pathogens in MEF samples.